2016
DOI: 10.1186/s13046-016-0432-x
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of miR-501-5p activates the wnt/β-catenin signaling pathway and enhances stem cell-like phenotype in gastric cancer

Abstract: BackgroundmiRNAs are critical post-transcriptional regulators of gene expression and key mediators of tumourigenesis. miR-501-5p is newly identified to be involved in the tumor progression, but its biological role and mechanism remain largely unknown. This study is aimed to study the role of miR-501-5p in the progression of gastric cancer.MethodsReal-time PCR analysis was used to determine miR-501-5p expression in gastric cancer cell lines, clinical tissues and 112 clinicopathologically characterized gastric c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 33 publications
0
68
1
Order By: Relevance
“…Based on this observation, it is tempting to speculate that TERT , a crucial gene for life, regulates and is regulated by miRNAs of the same cluster. In line with this speculation, MIR500A and all downstream miRNAs of the cluster, act as oncomiRs and are related to different cancer types: MIR500A in hepatocellular carcinoma, gastric and breast cancer (26-28), MIR362 in chronic myeloid leukemia (29), MIR501 in gastric cancer (30), MIR660 in breast cancer (31) and MIR502 in colorectal and prostate cancer (32, 33). Conversely, the miRNAs located upstream MIR500A act as tumor suppressors: MIR532 inhibits the expression of TERT in ovarian cancer, resulting in decreased cell proliferation and invasion capacity (34), and MIR188 is down-regulated in oral squamous cell carcinoma (35).…”
Section: Discussionmentioning
confidence: 69%
“…Based on this observation, it is tempting to speculate that TERT , a crucial gene for life, regulates and is regulated by miRNAs of the same cluster. In line with this speculation, MIR500A and all downstream miRNAs of the cluster, act as oncomiRs and are related to different cancer types: MIR500A in hepatocellular carcinoma, gastric and breast cancer (26-28), MIR362 in chronic myeloid leukemia (29), MIR501 in gastric cancer (30), MIR660 in breast cancer (31) and MIR502 in colorectal and prostate cancer (32, 33). Conversely, the miRNAs located upstream MIR500A act as tumor suppressors: MIR532 inhibits the expression of TERT in ovarian cancer, resulting in decreased cell proliferation and invasion capacity (34), and MIR188 is down-regulated in oral squamous cell carcinoma (35).…”
Section: Discussionmentioning
confidence: 69%
“…The VEGF receptor is required in response to VEGF-dependent cell survival via EMT in colon carcinoma cell lines [40,41]. Additionally, miR-200 families are well-known miRNAs that regulate Wnt/β-catenin signaling [34] and also directly regulate EMT by targeting transcriptional repressors of ZEB1 and ZEB2, which regulate CDH1 expression [42,43]. These results indicate that the miRNAs we identified may play an important role in both high-and low-risk subtypes.…”
Section: Gsea Kegg Pathway Analysis and Go Analysismentioning
confidence: 65%
“…KEGG pathway analysis showed that fatty acid metabolism, oxidative phosphorylation, valine, leucine, and isoleucine degradation pathways were significantly different. For the miRNA, miR-501 that activates Wnt/β-catenin signaling in gastric cancer and colorectal cancer [34,35] and tumor suppressor miR-26 that has been reported to regulate the Wnt/β-catenin signaling in prostate cancer and cholangiocarcinoma [36] were significance between subtypes. Intriguingly, miR-26 is also known to contribute TGF-β-induced EMT [37] and inflammation response [38], which could be associated with the low-risk subtype.…”
Section: Gsea Kegg Pathway Analysis and Go Analysismentioning
confidence: 96%
“…Another study by Lin et al [137] demonstrate that nanoformulation of miR-34a successfully removes BCSCs via targeting C22ORF28 (chromosome 22 open reading frame 28), which act as a direct and functional target of TV-miR-34a. By using hTERT promoter-driven VISA delivery of miR-34a plasmid, they further showed TV-miR-34a markedly suppressed tumor-initiating properties of BCSC in vitro and in vivo and also reported that TV-miR-34a plasmid synergizes with docetaxel for eradicating BCSC by targeting C22ORF28 [96]. miR-628, another important miRNA deregulated in human cancer pathogenesis, has been shown to suppresses BCSC stemness features by targeting Ras/Rac guanine nucleotide exchange factor 1 (SOS1) [138].…”
Section: Breast Cancermentioning
confidence: 96%